ナンキョク ロケット S-210JA-29ゴウキ ニヨル セイオンジ カブ デンリソウ デンバ ノ カンソク b. デンバ ト デンリュウ ケイ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 小川, 俊雄; オガワ, トシオ; 岩上, 直幹; イワガミ, ナオミキ; 鮎川, 勝; アユカワ, マサル; OGAWA, Toshio; IWAGAMI, Naomiki; AYUKAWA, Masaru (1980)
P(論文) 1977年7月12日16時15分に,昭和基地から発射された観測ロケットS-210JA-29号機に搭載した球ダブルプローブを用いて,118kmまでの下部電離層中で,地磁気静穏時の静電場とAC(18-220 Hz)電場を観測した.電子密度が2-3×10^4 cm^<-3>のE層下部で観測した静電場は約10 mV/mであったが,一方,約110kmより上の高度で電場は急激に増大して約130mV/mに達し,電子密度の減少によく対応した.また全高度でごく弱いACノイズが観測された. Quiet-time DC and AC (18-220 Hz) electric fields were observed in the lower ionosphere up to 118 km by means of spherical double probes on board the sounding rocket S-210JA-29 which was launched from Syowa Station at 16.15 UT on July 12, 1977 The DC electric field intensity was～10 mV/m in the lower E region where the electron density was 2-3×10^4 cm^<-3>, while it increased sharply up to ～130 mV/m above the altitude of ～110 km with a good correlation with the decrease in the electron density. 0nly weak AC noise was observed in the whole altitude range departmental bulletin paper